2002
DOI: 10.1128/aac.46.2.531-533.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sterol and Fatty Acid Composition ofCandida lusitaniaeClinical Isolates

Abstract: The sterol and fatty acid compositions of four amphotericin B-resistant and of two amphotericin Bsusceptible Candida lusitaniae clinical isolates were determined. A flow cytofluorometric susceptibility test (FCST) with a membrane potential-sensitive cationic dye was used as a complement to the conventional method for selecting the isolates. Compared to susceptible isolates, resistant ones showed a greatly reduced ergosterol content and changes in sterol composition, consistent with a defect in ⌬837 isomerase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Although the sterol composition of C. albicans has been studied before (44)(45)(46), a more detailed analysis of the amounts and identities of minor sterols has not been carried out. The wild-type cells contained a sterol composition typical of ascomycetous fungi (47), with many of the same sterols reported by other investigators for C. albicans.…”
Section: Resultsmentioning
confidence: 99%
“…Although the sterol composition of C. albicans has been studied before (44)(45)(46), a more detailed analysis of the amounts and identities of minor sterols has not been carried out. The wild-type cells contained a sterol composition typical of ascomycetous fungi (47), with many of the same sterols reported by other investigators for C. albicans.…”
Section: Resultsmentioning
confidence: 99%
“…Although this phenomenon has been known and noted for more than 25 years (24), the genetic mechanism(s) for this acquired resistance is not well understood. There are data supporting the presence of gene mutations in the ergosterol biosynthetic pathway, thereby blocking production of the binding target, i.e., ergosterol (4,17). A mutation mechanism(s) is credible since C. lusitaniae is a haploid yeast and nonlethal mutations can have a direct effect on gene expression.…”
mentioning
confidence: 99%
“…One study found a correlation between amphotericin B resistance and sterol composition consistent with a defect in the ⌬8-7 isomerase Erg2 (38,39), which can also result in amphotericin B resistance in C. albicans and C. neoformans (8,27), but overall, there is limited information on the genome of C. lusitaniae, and there have not been any specific attempts to identify genes in the ergosterol biosynthetic pathway.…”
mentioning
confidence: 99%